The role of ROX and mROX indices in predicting intubation in COVID 19 patients treated with high flow nasal oxygen in Intensive Care Unit - İlkay Ceylan; Halil Erkan Sayan; Korgün Ökmen; Umut Öylevi (National Scientific Medical Center, 2021)
Aim: In Coronavirus disease 2019 (COVID-19)-related respiratory failure, high-flow nasal oxygen (HFNO) therapy may delay invasive ventilation. The respiratory rate oxygenation (ROX) and modified ROX (mROX) indices, which can predict the need for invasive ventilation, can also be used in patients with COVID-19 with respiratory failure. The aim of the study was to verify the effectiveness of ROX and mROX to predict entubation need in HFNO therapy patients in intensive care unit. Material and Methods: This retrospective study included 41 patients in the final evaluation. Results: The overall mortality of patients with similar demographic and laboratory data was 60,97%. Invasive ventilation was required in 27 patients. The cutoff values for prediction of intubation for ROX and mROX at 6 h were determined as 4,95 and 6,01. Conclusion: These indices can predict the need for invasive ventilation during the follow-up of COVİD 19 patients who under go HFNO and can help prevent adverse outcomes.